THE EFFECT OF PROMOTION AND PRODUCT QUALITY ON MEMBER DECISIONS USING MUDHARABAH PRODUCTS WITH INTEREST AS INTERVENING VARIABLES - Saputra, Rifqi Dzakwan; Firmansyah, Fani (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to analyze the influence of promotion and product quality on members' decisions to use mudharabah products with interest as an intervening variable for members of the Baitul Maal wa Tamwil Sarana Entrepreneurial Muslim Malang. This study uses quantitative research methods using secondary data in the form of questionnaires. The technique used to determine the sample in this study is the technique of simple random sampling, with a sample of 80 members of the Baitul Maal wa Tamwil Muslim Entrepreneur Facility Malang. The data analysis tool in this study uses the software SmartPLS. Promotion, product quality, and interest influence the decisions of members of the Baitul Maal wa Tamwil Sarana Entrepreneurial Muslim Malang in using mudharabah products. 75.2% of the decision variables are influenced by promotions, product quality, and interest, while the remaining 27.5% are influenced by other variables. Promotion and product quality also influence the interest of the Baitul Maal wa Tamwil Facility of Malang Muslim Entrepreneurs in using mudharabah products. 58.5% of the interest variable is influenced by promotion and product quality, while the remaining 41.5% is influenced by other variables. Interest is also able to mediate the relationship between promotions and decisions, then interest is also able to mediate the relationship between product quality and the decisions of members of the Baitul Maal wa Tamwil Sarana Entrepreneurial Muslim Malang in using mudharabah products. The contribution of this research is to know how the influence of promotion and product quality owned by Baitul Maal wa Tamwil Malang Muslim Entrepreneur Facility in attracting its members.